2009
DOI: 10.1534/genetics.108.098277
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Accuracy From Genomic Selection in Populations Derived From Multiple Inbred Lines: A Barley Case Study

Abstract: We compared the accuracies of four genomic-selection prediction methods as affected by marker density, level of linkage disequilibrium (LD), quantitative trait locus (QTL) number, sample size, and level of replication in populations generated from multiple inbred lines. Marker data on 42 two-row spring barley inbred lines were used to simulate high and low LD populations from multiple inbred line crosses: the first included many small full-sib families and the second was derived from five generations of random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
307
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(332 citation statements)
references
References 23 publications
19
307
0
6
Order By: Relevance
“…The comparison between BL and RKHS yielded mixed results; this finding is in agreement with those of Zhong et al (2009), who evaluated different models in different scenarios (mating systems) and did not find one method that performed best across scenarios. For grain yield and anthesis-silking interval, RKHS methods performed either similarly or better than the BL; however, for female and male flowering traits in maize, BL outperformed RKHS markedly.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The comparison between BL and RKHS yielded mixed results; this finding is in agreement with those of Zhong et al (2009), who evaluated different models in different scenarios (mating systems) and did not find one method that performed best across scenarios. For grain yield and anthesis-silking interval, RKHS methods performed either similarly or better than the BL; however, for female and male flowering traits in maize, BL outperformed RKHS markedly.…”
Section: Discussionsupporting
confidence: 84%
“…Several simulation studies (Bernardo and Yu 2007;Wong and Bernardo 2008;Mayor and Bernardo 2009;Zhong et al 2009) have reported important gains in genetic progress associated with the use of GS in plant breeding. Recently, Heffner et al (2009) concluded that the high correlation between true breeding values and the genomic estimated breeding values found in several simulation studies is sufficient for considering selection based on molecular markers alone; however, evaluation of these methods with real plant data is still very limited.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that depending on the frequency of re-estimating the effects, different methods may be more suitable to obtain SNP effects whose accuracies are more persistent across generations. For instance, methods that are better able to disentangle between LD and linkage information show better persistency of GEBV accuracy across generations (Habier et al, 2007;Zhong et al, 2009). Despite the finding that approximately 50 000 SNPs are sufficient for within-breed genomic breeding value prediction in cattle, larger SNP arrays that undoubtedly will become available in the future will increase the LD between SNPs and QTL, leading to slower reduction of the accuracy of GEBVs across generations.…”
Section: Persistency Of Ld and Accuracy Of Gebvs Across Generationsmentioning
confidence: 99%
“…The recent availability of genomewide dense SNP marker maps has made GS with real data feasible. Studies of the accuracy of genomic predictions have emerged in some animal species, including mice (Lee et al 2008;Legarra et al 2008), chickens (GonzalezRecio et al 2009), and cattle , and in plant species [for example, barley (Zhong et al 2009)]. For GS applied to dairy cattle, accuracies for the GW-EBV have been reported in North American Holstein (VanRaden et al 2009), Australian Holstein-Friesian , and New Zealand Holstein-Friesian and Jersey dairy cattle (Harris et al 2008).…”
Section: G Enomic Selection (Gs) Is a New Technology Thatmentioning
confidence: 99%